Analisis Sensitivitas Sensor GY-ML8511 dalam Deteksi Formalin - Ramadhan, M. Farhan; Yusfi, Meqorry; Harmadi, Harmadi (Universitas Andalas, 2024)
Food safety is a crucial aspect in meeting people's nutritional needs. Formalin, a dangerous preservative, is often used illegally to extend the shelf life of foodstuffs, posing serious risks to consumer health. This research develops a portable technology for rapid detection of formaldehyde in foodstuffs. The method utilizes the interaction between UV light and the concentration of formaldehyde in a sample treated with Schiff reagent, enabling the measurement of UV uptake proportional to formaldehyde concentration. The Schiff reagent reacts with formalin to produce a colored compound whose absorbance is measured to detect and quantify formalin in the sample. The designed optical system focuses on measuring the intensity of light from a UV LED source, which is then transmitted through the sample. The successfully transmitted light intensity is converted into an electrical signal by the GY-ML8511 sensor, which is then processed by the NodeMCU ESP8266 to display the concentration of formalin on the LCD screen. This research also analyzes the sensitivity and selectivity of the GY-ML8511 sensor to evaluate its performance and reliability in detecting formaldehyde, with the ultimate goal of improving food safety through innovative detection technologies, such as the use of biosensors and advanced spectroscopy. This technology contributes to existing solutions by enabling rapid and accurate detection at various stages of food production, thereby reducing the risk of contamination and improving compliance with food safety standards